Ambulatory Cardiology Telemedicine: A Large Academic Pediatric Center Experience. (October 2021) - Phillips, Aaron A; Sable, Craig A; Atabaki, Shireen M; Waggaman, Christina; Bost, James E; Harahsheh, Ashraf S
We performed a retrospective study of cardiology telemedicine visits at a large academic pediatric center between 2016 and 2019 (pre COVID-19). Telemedicine patient visits were matched to data from their previous in-person visits, to evaluate any significant differences in total charge, insurance compensation, patient payment, percent reimbursement and zero reimbursement. Miles were measured between patient's home and the address of previous visit. We found statistically significant differences in mean charges of telemedicine versus in-person visits (2019US$) (172.95 vs 218.27, p=0.0046), patient payment for telemedicine visits versus in-person visits (2019US$) (11.13 vs 62.83, p≤0.001), insurance reimbursement (2019US$) (65.18 vs 110.85, p≤0.001) and insurance reimbursement rate (43% vs 61%, p=0.0029). Rate of zero reimbursement was not different. Mean distance from cardiology clinic was 35 miles. No adverse outcomes were detected. This small retrospective study showed cost reduction and a decrease in travel time for families participating in telemedicine visits. Future work is needed to enhance compensation for telemedicine visits.